Manajemen Mutu Pendidikan Dalam Meningkatkan Prestasi Peserta Didik Di Madrasah Aliyah Negeri Kota Batu - Albab, Shobich Ulil; Muslimin, Imam; Zuhriyah, Indah Aminatuz; Hernawati, Susi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Student achievement is a benchmark that an educational institution can be categorized as having superior quality. Educational institutions that have superior quality cannot be realized if they are not supported by good management. For this reason, it is necessary to apply management in order to improve the quality of education, so as to encourage increased student achievement. There are important indicators in education quality management, namely raw input, process and output, the need for educational institutions to pay attention to these 3 aspects so that the quality of education can be realized. Raw input related to the process of accepting new students, or recruitment is the beginning in determining the quality of prospective students who will take part in the learning process. Some of the stages in raw input are the most important part, this section includes determining the criteria for prospective students, which at its peak is the class division stage, which must be really adjusted to the level of ability of students. In addition to learning, the process is at the heart of improving quality, how an educational institution can process it into products that are ready to be marketed in society. Process is a determinant, that is where educational institutions have superior quality. Output is the result obtained through the educational process. Basically, there are important indicators that educational institutions can be said to have superior quality, among others, these indicators include academic and non-academic achievements, as well as the level of community satisfaction.